CONTRASTIVE STUDY OF PROVERBS WITH ANTHROPONYMIC COMPONENTS IN ENGLISH AND UZBEK LANGUAGES (TAMADDUN NURI JURNALI, 2025)
Proverbs are an integral part of a language’s cultural and linguistic heritage. This study focuses on proverbs containing anthroponymic components in English and Uzbek, examining their linguistic structure, cultural significance, and semantic peculiarities. Through a comparative analysis, the study highlights similarities and differences in the use of anthroponyms within proverbial expressions in both languages, revealing underlying cultural values and historical influences.